Statistical analysis of geochemical data: a tool for discriminating between kaolin deposits of hypogene and supergene origin, Patagonia, Argentina - Cravero, Fernanda (2010)
The numerous kaolin deposits located in Patagonia, Argentina, have been formed by hypogene or supergene processes. The primary origin has been established from O18 and D isotopic composition of the main minerals, kaolinite and/or dickite, and from the behaviour of certain elements during the alteration. The aim of this paper was to find if there is a tool, other than oxygendeuterium data, to establish the origin of the Patagonian kaolin deposits. To handle the large number of variables per sample, a statistical multivariate study was used. The Principal Component method defines, on one hand the variables that better characterize each deposit and, on the other hand, the correlation between them. Fifty seven elements were considered and those that were not explained using these two components (which represent 75% of the total variance of the model) were discarded. As a result, the contents of Fe2O3, P2O5, LOI, Sr, Y, Zr, V, Pb, Hf, Rb, S and REE were used and the results show that the two components separate the deposits into two fields that are consistent with the process of formation. The first component indicates that Fe2O3, Y, Rb, U and HREE are more abundant in the supergene deposits, whereas, Sr, Pb, S and V are more abundant in the hypogene deposits. The second component shows that S, P2O5 and the LREE are enriched in the hydrothermal deposits, whereas Zr is more abundant in those formed under weathering conditions.